Influence of previous Zika virus infection on acute dengue episode. - Cassia F Estofolete; Alice F Versiani; Fernanda S Dourado; Bruno H G A Milhim; Carolina C Pacca; Gislaine C D Silva; Nathalia Zini; Barbara F Dos Santos; Flora A Gandolfi; Natalia F B Mistrão; Pedro H C Garcia; Rodrigo S Rocha; et al. (Public Library of Science (PLoS), 2023)
Background The co-circulation of flaviviruses in tropical regions has led to the hypothesis that immunity generated by a previous dengue infection could promote severe disease outcomes in subsequent infections by heterologous serotypes. This study investigated the influence of antibodies generated by previous Zika infection on the clinical outcomes of dengue infection. Methodology/principal findings We enrolled 1,043 laboratory confirmed dengue patients and investigated their prior infection to Zika or dengue. Severe forms of dengue disease were more frequent in patients with previous Zika infection, but not in those previously exposed to dengue. Conclusions/significance Our findings suggest that previous Zika infection may represent a risk factor for subsequent severe dengue disease, but we did not find evidence of antibody-dependent enhancement (higher viral titer or pro-inflammatory cytokine overexpression) contributing to exacerbation of the subsequent dengue infection.